Effect of pH on biomass production and carbohydrate accumulation of Chlorella vulgaris JSC-6 under autotrophic, mixotrophic, and photoheterotrophic cultivation. (May 2022) - Cheng, Chieh-Lun; Lo, Yung-Chung; Huang, Kai-Lou; Nagarajan, Dillirani; Chen, Chun-Yen; Lee, Duu-Jong; Chang, Jo-Shu
Graphical abstract: Highlights: Chlorella vulgaris JSC-6 is capable of assimilating acetate and butyrate. Fatty acid assimilation by JSC-6 was pH dependent. Low pH (6.5) was not optimal for autotrophic, photoheterotrophic or mixotrophic modes. Autotrophic and mixotrophic modes attained 49–50% carbohydrates by dry weight. Glucose was the predominant sugar in the microalgal carbohydrates. Abstract: Microalgal biomass, known as the third generation feedstock for biofuels production, is currently being explored mainly for lipids and functional components. However, the potential of microalgal carbohydrates has not been evaluated. In this investigation, Chlorella vulgaris JSC-6 was used for carbohydrates production from CO2 and fatty acids under different cultivation strategies to meet the requirements of a CO2 -neutral and clean fermentation system for biofuel production. Autotrophic cultivation resulted in better carbon assimilation and carbohydrate accumulation; about 1.4 g CO2 could be converted to 1 g biomass, of which 50% are carbohydrates. Assimilation of fatty acids in photoheterotrophic and mixotrophic modes was influenced by pH, and pH 7–7.5 supported butyrate and acetate assimilation. The maximum carbohydrate content (49.86%) was attained in mixotrophic mode, and the ratio of the simple sugars glucose-xylose-arabinose was 1:0.11:0.02. The higher glucose content makes the microalgal biomass a suitable feedstock for sugar-based fermentations.